Antigenic variation and its evolution in P. falciparum malaria - Noble, RJ (2014)
This thesis investigates antigenic variation and its evolution in Plasmodium falciparum, the cause of the most deadly form of human malaria. Antigenic variation is a strategy for evading immunity by switching between antigenic variants during infection. In P. falciparum, such variable antigens confer different binding phenotypes that may affect parasite survival and have also been linked to pathology. Here, a new statistical method is described for determining the switching patterns that underlie antigenic variation. This method is then applied to experimental data to yield a full description of an antigenic switching network in P. falciparum. In light of the findings, theoretical modelling is used to show how immune selection and binding phenotypes may have contributed to the evolution of antigenic repertoire structure, expression order and virulence. Related models are also used to investigate parasite population diversity, providing possible explanations for observations reported here and elsewhere, with implications for vaccine design. Together, these chapters advance understanding of P. falciparum immune evasion and how it relates to pathology. This work further reinforces the role of host immunity in shaping pathogen population diversity at multiple levels.